THE LEGAL CONSEQUENCES OF CONSTITUTIONAL COURT DECISION NO. 18 OF 2014 ON THE ENFORCEMENT OF CRIMINAL LAW CONCERNING HAZARDOUS AND TOXIC WASTE AGAINST CORPORATIONS - Chistopher Kendrick Adam; Benny Djaja (LPPM Universitas Ekasakti Padang, 2023)
This research aims to examine the legal consequences of Constitutional Court Decision No. 18 of 2014 regarding the case of hazardous and toxic waste against corporations. Furthermore, the study also analyzes the enforcement of criminal law concerning hazardous and toxic waste against corporations after the Constitutional Court's decision. The Constitutional Court's Decision No. 18 of 2014 has significant implications for the enforcement of criminal law concerning hazardous and toxic waste by corporations. It provides guidance and limitations on how the law should be interpreted and applied in cases related to environmental offenses committed by corporations. The research will focus on evaluating the post-decision enforcement of criminal law against corporations involved in hazardous and toxic waste cases. It will examine the roles of law enforcement agencies, such as the police, prosecutors, and the judiciary, in investigating, prosecuting, and adjudicating cases involving corporations and hazardous waste. Additionally, the study will explore the protection of human rights and access to justice for victims affected by hazardous and toxic waste. It will also investigate preventive measures and regulatory frameworks aimed at deterring environmental offenses by corporations. The research will employ a combination of legal analysis, case studies, and comparative studies to examine the effectiveness of the enforcement of criminal law in light of the Constitutional Court's decision. It will contribute to the understanding of the legal implications and challenges faced in prosecuting and holding corporations accountable for hazardous and toxic waste.